Способи реалізації імпліцитної відмови у контексті сучасних політичних процесів в Україні - Одарчук, Наталія Андріївна; Мірончук, Тетяна А.; Odarchuk, Nataliia A.; Mironchuk, Tetiana A. (Маріупольський державний університет, 2017)
У статті розглядається явище імпліцитності та особливості його прояву у відмові. На основі промов політичних діячів, виголошених стосовно сучасних процесів в Україні, виокремлюються способи реалізації імпліцитної відмови. З’ясовується її важливість у політичному дискурсі задля уникнення конфліктів. Виділяються мовні тактики, до яких вдаються іноземні політики для непрямого вираження відмови. The article deals with the implicit refusal and peculiarities of its implementation in the political discourse. The research is based on the speeches of the representatives of the world political elite delivered in the context of the latest political processes in Ukraine. Since reestablishing its independence in 1991 Ukraine has been trying to play a notable role in the world politics. It has particularly become noticeable after the Revolution of Dignity in 2014, which was followed by a series of political, social and economic changes in the country. However, Ukraine has not become an equal member of the world politics yet, therefore has to turn to the stronger, more powerful states and the International Monetary Fund for the diplomatic and financial support. It is quite natural that not all requests of such kind are to be satisfied, but the essence and peculiarity of the political negotiations is using maximum of diplomacy and keeping face even in case of refusal. Because of this fact the latter (refusal) in most political speeches is implicit, latent, and tacit, so the article is aimed at recognizing and deciphering it. The main criterion of implicitness is absence of direct expression of utterance content. Since implicit information is objectified indirectly for it to be understood it is essential to attract cognitive process of guessing and base it on the context, speech situation as well as extralinguistic means. Implicit refusal in the political discourse functions as a means of avoiding conflict situations between the speakers. Straightforward «no» would violate the principle of linguistic politeness and could cause a conflict, while the author of implicit refusal demonstrates his absence of intention to start any, on the contrary, tries to use all the diplomatic means to divert controversy. The patterns of implicit refusal are not generally accepted; they are unique in speech and are dependent on the personality of the speaker as well as the communicative context. The analysis of the speeches of foreign politicians concerning the processes in Ukraine has enabled to single out the tactics they resort to and by which implicit refusal is realized. They are as follows: tactic of changing the subject of communication; tactic of digression from the answer; tactic of persuasion; tactic of warning; tactic of rhetorical question. Due to their mediate character these linguistic means of expressing implicit refusal make the message with negative content milder and more tactful. As a result they guarantee stability in the political communication between Ukraine and its strategic partners.
Ways of realization of implicit refusal in the context of political processes in Ukraine
Keywords: відмова; імпліцитність; тактика; політична комунікація; дипломатичність; конфлікт; refusal; риторичне запитання; implicitness; tactics; political communication; diplomacy; conflict; rhetorical question